Pelatihan Sekolah Tangguh Bencana Sebagai Upaya Peningkatan Kewaspadaan Pada SMAN 10 Bandarlampung - Ajeng Savitri Puspaningrum; Dian Pratiwi; Imannuel Ricky Destianto; Guntur Wibisono (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Located in a residential area and prone to disasters such as earthquakes and tsunamis, SMA Negeri 10 Bandar Lampung is at risk of being affected by collapsed buildings and fires. School buildings, which are multi-story, also add to the risks that can be caused. The unavailability of adequate evacuation maps and the absence of mitigation training for the existing academic community can also increase the risks arising from disasters that may occur at any time. To reduce this risk, disaster mitigation training was conducted for the academic community and preparation of evacuation maps. This activity increased the trainees’ knowledge by 48.8% so that the academic community at SMA Negeri 10 Bandar Lampung would be more prepared to mitigate in the event of a disaster.